The Association for Human Pharmacology in the Pharmaceutical Industry London Meeting 2018: Brexit and Other Challenges in Early Phase Drug Development - Reijntjes, Susan; Albayaty, Muna; Bush, James; Cheriyan, Joseph; Cromie, Anthea; Koch, Annelize; Hammond, Michael; Mair, Stuart; Scholes, Peter; Lorch, Ulrike; Stringer, Steffan; Taubel, Jorg; et al. (Frontiers in Pharmacology, 2018)
The Association for Human Pharmacology in the Pharmaceutical Industry (AHPPI) annual meeting focused on the changing face of early phase drug development and opened with a keynote speech concerning the revolution in pharmaceutical medicine over the last 30 years. Examples were presented of how translational pharmaceutics is being used to tackle the high drug candidate failure rate and is improving productivity when moving drug candidates from the laboratory through to clinical proof of concept. The EU Medicines Agency revised 2007 Risk Mitigation guideline on first in human (FIH) clinical trials was discussed. The focus of the revised guideline, which came into force in February 2018, is on risk mitigation and promotion of safety and will assist drug sponsors with the design and performance of early clinical studies. The use of integrated adaptive protocol designs in early clinical development was discussed in relation to the challenges involved when running early phase clinical trials in patients. The Health Regulatory Authority presented its strategies to ensure that the UK remains an attractive place to conduct Phase I trials. They confirmed that in the event of a ‘no deal’ Brexit, it is well placed to implement and influence many provisions of the new EU CTR. The meeting provided an opportunity to discuss the changing regulatory environment and the opportunities and challenges facing the UK following Brexit with invited speakers from a range of disciplines including drug development, clinical trials and research organizations, government science policy and regulatory agencies.